Modelagem hidrológica distribuída e seu uso no monitoramento de secas e avaliação dos impactos das mudanças climáticas nas vazões afluentes a reservatórios - Bezerra, Jorgiane Pires (2024)
Extreme hydrological events have intensified in response to climate change, marked by significant rises in global temperature and changes in precipitation patterns. These changes have not only exacerbated the severity of droughts and floods but have also altered their spatial pattern. Against this backdrop, the semi-arid region of Ceará, located in northeastern Brazil, has become the focus of studies and the development of water resource management strategies due to its particular susceptibility to climate variations. This study proposed the creation of tools, using distributed hydrological modelling, to support the study and monitoring of droughts, as well as assessing the effects of climate change on the flow regime, focusing on the Banabuiú Hydrographic Region. A Composite Drought Index (CDI) was developed and applied specifically to this region, and later validated in the Riacho do Sangue Reservoir Basin. This index integrates six climatic and hydrological indicators, offering an integrated assessment of drought conditions. The weighting of the indicators for the composition of the CDI was conducted through the results of a Principal Component Analysis (PCA) of the indicators. To assess the effects of climate change on the region's hydrology, the relative changes in flows were analyzed, assessing both the probability of reduction and the changes in floods, considering different frequencies of occurrence. For this analysis, global climate models from CMIP6 were used, allowing an investigation of future projections under various climate scenarios. The results confirmed the effectiveness of the CDI as a tool for monitoring droughts, demonstrating its ability to capture the severity and duration of these events on different time scales. The analysis of the impacts of climate change has revealed a significant variation in flow projections depending on the analyzed period and future scenario. This phenomenon is accompanied by an increase in uncertainty associated with the results, as some indicate an increase in flow while others point to a decrease. This factor is primarily attributed to differences between climate models and emission scenarios. It is concluded that the implementation of the CDI and the analysis of variability and uncertainty in flows constitute significant advances in monitoring and understanding the impacts of climate change on extreme hydrological events, especially in semi-arid regions. By integrating various hydrological and climatic indicators, the CDI becomes a tool for detecting and assessing droughts, serving as an instrument to support public policies and drought management initiatives. At the same time, the study on the variability and uncertainty of flows underlines the need to incorporate these aspects into water resources planning.